(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article is devoted to the limitation of traumatic brain injury. Morphologically, they often manifested as epi-, subdural, and subarachnoid hemorrhages. By the nature of morphological changes, in particular, the state of hemorrhage, the presence of a convolution, color, organization or resorption, density and a number of other signs, it is possible to definitely establish the prescription of injury.